The Role of the Kapuas River in Shaping Social Interaction and Cultural Acculturation in Multicultural Communities - Tata Ihsan; Pariatman Tanjung; Embun Afifah Honey; Mega Amanda; Dewi Cindia Putri; M Zainul Hafizi (CV. Yazri Aksara Nusantara, 2025)
Purpose – This study investigates the role of the Kapuas River not only as a geographical element but also as a vital social and cultural space in shaping social interaction and cultural acculturation within Pontianak's multicultural urban community. The research addresses the lack of studies exploring the river's symbolic and sociocultural dimensions, aiming to enrich the discourse on spatial identity and interethnic relations in riparian urban settings Design/methods/approach – A descriptive qualitative approach was used, involving participatory observation, in-depth interviews with local residents from various ethnic backgrounds, and documentation of everyday cultural and social activities along the riverbanks. The collected data were analyzed thematically to identify patterns of interaction and cultural blending Findings - The findings reveal that the Kapuas River facilitates dynamic intercultural interactions, where daily activities such as floating markets, joint religious festivals, and shared culinary traditions contribute to strengthening social cohesion and constructing a hybrid cultural identity. The study confirms that the river functions as a symbolic corridor mediating social integration and cultural negotiation among diverse urban groups. Research implications/limitations – The study is limited to the eastern part of Pontianak and may not fully represent the entire sociocultural dynamics along the Kapuas River. The qualitative nature of the research emphasizes depth over breadth, and future studies employing mixed methods or covering wider geographical areas are recommended. Nonetheless, this study provides a foundation for integrating cultural-spatial considerations into inclusive urban development and river governance models.